Handling Failures in Data Quality Measures - Abdul Aziz, Azwa; Emran, Nurul A.; Abdullah, Noraswaliza (2013)
Successful data quality (DQ) measure is important for many data consumers (or data guardians) to decide on the acceptability of data of concerned. Nevertheless, little is known about how “failures” of DQ measures can be handled by data guardians in the presence of factor(s) that contributes to the failures. This paper presents a review of failure handling mechanisms for DQ measures. The failure factors faced by existing DQ measures will be presented, together with the research gaps in respect to failure handling mechanisms in DQ frameworks. We propose ways to maximise the situations in which data quality scores can be produced when factors that would cause the failure of currently proposed scoring mechanisms are present. By understanding how failures can be handled, a systematic failure handling mechanism for robust DQ measures can be designed.